Defensive actions of world top judoists - Boguszewski, D. (Journal of Human Kinetics, 2011)
The objective of this work was to define and determine the effectiveness of defensive actions applied in judo fighting. The study was based on recordings of final fights from Olympic Games, World Championships and World Cup (2005-2008). Actions of female and male contestants participating in total of 56 fights were analyzed (to an accuracy of 10-second-periods of time). All actions, including attacks, counter-attacks and defense without counterattack, were recorded and their effectiveness, preparatory actions, breaks and the referees` decisions were evaluated. Altogether fights of 95 contestants were subjected to analysis. According to the author`s classification of defensive actions, 12 types of defense without counter-attack were defined as follows: (1) hand block, (2) hip block, (3) maneuvering around, (4) twist onto abdomen, (5) hand and hip block, (6) hand block and maneuvering around, (7) stepping aside, (8) separation from grasp, (9) leaving the mat, (10) leg entanglement, (11) bridge, (12) return to tachiwaza (escape from ne-waza). Types of defense most often applied according to the study - hand block and twist onto abdomen - were the least effective (93% and 70% respectively). Ashi-waza and te-waza were throws most often applied as counter-attack. However, sutemi-waza throws were most effectively (50%) applied. Highly effective counter-attacks (28%) should serve as a clue for coaches and athletes at the competitive level. The rules set forth by professor Jigoro Kano (among others: "give up in order to win") may not be adequate for today`s competition.